Optimization And Analysis Of Copper Wire Raw Material Inventory For Magnetic Process With Dynamic Programming Method - Annisa Indah Pratiwi; Akda Zahrotul Wathoni; Dewih Adetia; Ahmad Ridho Nurohman (OPSI, 2021)
Inventory control is an important problem that is commonly faced by a company, because the presence of raw materials is very important for companies, therefore it is necessary to carry out good inventory control management in managing raw material inventory, raw materials are materials that are part of the finished product and can be identified to the finished product. One of the methods used to plan raw material control is to use dynamic programming methods. Before performing calculations with dynamic programming, it is necessary to forecast the use of raw materials for the next one year period, then dynamic program calculations can be done by making mathematical models, determining the objective function, constraint function, and recursive function of the problem at hand. This study aims to determine the raw material requirements of copper wire needed for production in the 2021 period. To optimize the supply of copper wire raw materials in order to minimize ordering costs, purchasing costs, and raw material storage costs.